A representação clerical da bruxaria no século XV: o livro V do Formicarius, de Johannes Nider - Tomazelli, Roni (2016)
In the first half of the fifteenth century, the Dominican theologian and reformer Johannes Nider was responsible for formulating a treaty with a strong doctrinal and moralizing content called the Formicarius (1436-1437). The document is part of deep reform movement of Christianity that occurred after the hardships experienced by European society throughout the fourteenth century and is among the first writings to present the outlines of the emerging concept and representation of demonic witchcraft. In the wake of religious, cultural and social transformations in the Western Europe, the magical and superstitious practices, understood in the High Middle Ages as illusions caused by the devil on people of little faith, received a new classification. Associated with the crime of heresy would form the demonic stereotype of witchcraft. This new malignancy model, based on the belief of the existence of a new group of devil worshipers who gathered in night meetings in which profaning the symbols and rituals of Christianity and committed the most execrable actions to mankind, served as justification to begin a witch hunt that took place between the fifteenth and seventeenth centuries. Our hypothesis is that the environment of fear and uncertainty raised by the fourteenth century inconstancy urged the Church in a relentless pursuit to identify this new enemy. The Church found the enemy ipso facto near the medieval minorities, individuals considered deviant and people with physical and moral stigmas that justified their exclusion. Therefore, we aim to understand the mechanisms of stigmatization of minorities within the medieval clerical discourse of demonization of witchcraft